Presence and genetic variability of Piscine orthoreovirus genotype 1 (PRV‐1) in wild salmonids in Northern Europe and North Atlantic Ocean. Issue 8 (28th May 2019) - Vendramin, Niccoló; Cuenca, Argelia; Sørensen, Juliane; Alencar, Anna L. F.; Christiansen, Debes H.; Jacobsen, Jan A.; Axen, Charlotte; Lieffrig, François; Ruane, Neil M.; Martin, Patrick; Sheehan, Timothy; Iburg, Tine M.; et al.
Abstract: Piscine orthoreovirus genotype 1 (PRV‐1) is widespread in farmed Atlantic salmon ( Salmo salar L.) populations in northern Europe, Canada and Chile. PRV‐1 occurs in wild fish in Norway and Canada; however, little information of its geographical distribution in wild populations is currently available, and the effect of PRV‐1 infection in wild populations is currently unknown. In this study, we present the findings of a survey conducted on 1, 130 wild salmonids sampled in Denmark, Sweden, Ireland, Faroe Islands, France, Belgium and Greenland between 2008 and 2017. PRV‐1 is reported for the first time in wild salmonids in Denmark, Sweden, Faroe Island and Ireland. The annual PRV‐1 prevalence ranged from 0% in France, Belgium and Greenland to 43% in Faroe Islands. In total, 66 samples tested positive for PRV‐1, including Atlantic salmon broodfish returning to spawn and Atlantic salmon collected at the feeding ground north of Faroe Islands. The phylogenetic analysis of S1 sequences of the PRV‐1 isolates obtained in this survey did not show systematic geographical distribution. This study sheds light on the spread and genetic diversity of the virus identified in populations of free‐living fish and provides rationale for screening wild broodfish used in restocking programmes.